The myth of symbiosis, psychotropy and transparency within the built environment. Issue 2 (17th May 2012) - Didakis, Stavros
Based on earlier studies of J. C. R. Licklider, this article translocates the context of symbiosis between man and the machine into the built environment, and more specifically into contemporary methods for the design of domestic/residential spaces. According to this, a discussion is made concerning the implementation of media and sensor technologies within the architectural DNA that initiate the emergence of psychotropic spaces of Ballardian Architecture; structures that are capable of becoming extensions of the inhabitant's mood, emotion and psyche. Furthermore, this article presents Plinthos Pavilion, a collaborative artwork that confronts issues of transparency, ubiquity and invisibility; an example of synergy between the primary notions of architectural and media design, which blend with the use of electronic and digital technology, transforming a physical structure to an organism that breathes, reacts and communicates.